A CCS busbar for energy storage battery module and a preparation method thereof
Patent Information
- Application Number
- CN202611390404.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-23
AI Technical Summary
二乙基次膦酸铝是常用的磷系阻燃剂,但其与高分子基体相容性差、易团聚、阻燃效率低
[0019]1、本发明采用硅烷偶联剂与2-甲基咪唑锌盐对二乙基次膦酸铝进行协同改性。硅烷偶联剂在二乙基次膦酸铝表面引入有机官能团,使填料表面由亲水性转变为亲有机性,改善了二乙基次膦酸铝与聚酯树脂基体的界面相容性,避免了由填料团聚而产生的应力集中,从而减少微裂纹引起的内聚破坏,增强了CCS母排的粘接强度;同时,2-甲基咪唑锌盐在高温下,锌离子氧化形成的氧化锌可作为物理屏障阻挡氧气进入燃烧区域,咪唑骨架分解产生的氨气和二氧化碳可稀释可燃气体浓度,锌离子在凝聚相中催化成炭,提高了CCS母排的阻燃效率。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy storage battery technology, specifically a CCS busbar for energy storage battery modules and its preparation method. Background Technology
[0002] The CCS integrated busbar is a core component in energy storage battery modules that connects battery cells in series and parallel and acquires voltage and temperature signals. In existing technologies, the CCS integrated busbar typically uses a thermo-pressed insulating film to encapsulate the copper busbar and signal acquisition components into a single thin-film structure.
[0003] Energy storage battery modules are exposed to high temperature and high humidity environments for extended periods, placing extremely high demands on the long-term stability of materials. Existing CCS integrated busbars suffer from low flame retardancy in their hot-pressed insulating films, leading to melt-through and short circuits. Furthermore, the adhesive layer is prone to hydrolysis and degradation under prolonged high temperature and humidity conditions, resulting in delamination, blistering, and other problems.
[0004] To improve the flame retardancy of CCS integrated busbars, most existing technologies employ the method of adding external flame-retardant sheets or simply adding phosphorus- or nitrogen-containing flame retardants to the adhesive. Aluminum diethylphosphonate is a commonly used phosphorus-based flame retardant, but it has poor compatibility with polymer matrices, is prone to agglomeration, and has low flame retardant efficiency.
[0005] In conclusion, in order to improve the flame retardancy of CCS integrated busbars and solve the aging problem under long-term high temperature and high humidity environments, it is of great significance to develop a CCS integrated busbar that can simultaneously meet the requirements of high flame retardancy, high bonding strength and long-term aging resistance. Summary of the Invention
[0006] The purpose of this invention is to provide a CCS busbar for energy storage battery modules and a method for its preparation, so as to solve the problems raised in the prior art.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] A CCS busbar for an energy storage battery module, comprising, from bottom to top, a hot-pressed insulating film, a copper busbar, a signal acquisition layer, and a hot-pressed insulating film, wherein the hot-pressed insulating film includes a polyethylene terephthalate (PET) base film and a hot-melt adhesive layer; the hot-melt adhesive layer comprises the following components, by weight: 60-85 parts polyester resin, 10-25 parts epoxy modified resin, 30-60 parts flame-retardant filler, 1-3 parts anti-hydrolysis agent, 2-6 parts curing agent, and 10-25 parts solvent; the flame-retardant filler is composed of modified aluminum diethylphosphinate, melamine polyphosphate, and magnesium hydroxide, wherein the mass ratio of modified aluminum diethylphosphinate, melamine polyphosphate, and magnesium hydroxide is (3-5):(2-4):(1-2); the modified aluminum diethylphosphinate is composed of... Aluminum diethylphosphonate is obtained by modification with silane coupling agent and 2-methylimidazolium zinc salt. The mass ratio of aluminum diethylphosphonate, silane coupling agent and 2-methylimidazolium zinc salt is 100:(1~5):(0.5~3). The preparation method of the modified aluminum diethylphosphonate is as follows: (1) 100 parts of aluminum diethylphosphonate are added to 100~110 parts of deionized water and stirred to disperse; (2) 1~5 parts of silane coupling agent are added and stirred at 300~500r / min for 20~40min, and the temperature is raised to 60~70℃ and stirred for 1~2h; (3) 0.5~3 parts of 2-methylimidazolium zinc salt are added, the temperature is raised to 70~80℃ and stirred for 2~12h, filtered, washed with ethanol, and vacuum dried at 70~80℃ to obtain modified aluminum diethylphosphonate.
[0009] More preferably, the silane coupling agent is any one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.
[0010] More preferably, the polyester resin is a saturated polyester resin; the epoxy modified resin is any one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and alicyclic epoxy resin; wherein γ-glycidoxypropyltrimethoxysilane is also known as γ-(2,3-epoxypropoxy)propyltrimethoxysilane, which are different names for the same compound.
[0011] More preferably, the anti-hydrolysis agent is any one or more of polymeric carbodiimide and monocarbodiimide; the curing agent is a blocked isocyanate.
[0012] A method for preparing a CCS busbar for an energy storage battery module, comprising the following steps:
[0013] S1: Take polyester resin, epoxy modified resin, blocked isocyanate, and solvent, stir to dissolve, add flame retardant filler and anti-hydrolysis agent, stir evenly to obtain adhesive coating liquid.
[0014] S2: Apply the adhesive coating liquid to one or both sides of the polyethylene terephthalate-based film, dry it to obtain a hot melt adhesive layer, cover the surface of the hot melt adhesive layer with a release film, and roll it up and cut it to obtain a hot-pressed insulating film.
[0015] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, copper busbar, signal acquisition layer, and hot-pressed insulating film in sequence. Hot-press, cool, discharge, and weld to obtain the CCS busbar.
[0016] In a more optimized manner, in S2, the drying temperature is 60~120℃ and the total drying time is 2~10min.
[0017] In a more optimized manner, in S3, the hot pressing temperature is 130~170℃, the hot pressing pressure is 1.0~3.0MPa, and the holding time is 60~180s.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. This invention employs a silane coupling agent and 2-methylimidazolium zinc salt to synergistically modify aluminum diethylphosphinate. The silane coupling agent introduces organic functional groups onto the surface of aluminum diethylphosphinate, changing the filler surface from hydrophilic to organic-philic, improving the interfacial compatibility between aluminum diethylphosphinate and the polyester resin matrix, avoiding stress concentration caused by filler agglomeration, thereby reducing cohesive damage caused by microcracks and enhancing the bonding strength of the CCS busbar. Simultaneously, at high temperatures, the zinc oxide formed by the oxidation of zinc ions in the 2-methylimidazolium zinc salt acts as a physical barrier to prevent oxygen from entering the combustion zone. The ammonia and carbon dioxide produced by the decomposition of the imidazolium skeleton can dilute the concentration of combustible gases, and the zinc ions catalyze char formation in the condensed phase, improving the flame retardant efficiency of the CCS busbar.
[0020] 2. This invention uses a flame-retardant filler prepared by compounding aluminum diethylphosphonate, melamine polyphosphate, and magnesium hydroxide in a mass ratio of (3~5):(2~4):(1~2). The phosphorus-containing free radicals generated by the thermal decomposition of aluminum diethylphosphonate capture H· and OH· free radicals in the gas phase, thereby interrupting the combustion chain reaction. Simultaneously, melamine polyphosphate expands upon heating in the condensed phase to form a dense carbon layer to isolate heat and oxygen transfer. Magnesium hydroxide dilutes the concentration of combustible gases through endothermic decomposition and the release of water vapor. This invention uses a ternary compounded flame-retardant filler to improve the flame-retardant efficiency of the CCS busbar.
[0021] 3. This invention improves the crosslinking density and hydrolysis resistance of the adhesive layer by crosslinking the epoxy modified resin with the polyester resin during the hot pressing process; at the same time, the carbodiimide anti-hydrolysis agent reacts with the carboxylic acid produced by polyester hydrolysis, preventing the continuous hydrolysis and improving the bonding stability of CCS busbar under long-term high temperature and high humidity environment. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] CCS (Cells Contact System) integrated busbars typically consist of copper or aluminum busbars, FPC (flexible printed circuit boards) or wire harnesses for voltage / temperature signal acquisition, plastic supports, and a thermoplastic insulating film that provides electrical insulation and structural bonding. Common plastic support materials include PPS (polyphenylene sulfide) and PBT (polybutylene terephthalate), both of which are characterized by high temperature resistance, moisture resistance, dimensional stability, and flame retardancy (up to UL94 V-0 rating), making them the standard choice for CCS support fabrication. Common insulating films include PET (polyethylene terephthalate) and PI (polyimide) films. PET film offers lower cost, better electrical insulation and heat resistance, while PI film provides higher temperature resistance and superior tear resistance. The copper or aluminum busbars are usually tin-plated to improve solderability and prevent oxidation and discoloration; the tin plating also reduces contact resistance. The plastic bracket has clips for securing it to the busbar; the FPC is fixed to the plastic bracket by heat pressing, which is a standard process in the field for integrating signal acquisition circuitry into the CCS busbar. All the above materials and structures are commercially available, and their specific specifications can be determined based on the battery module's voltage level, operating temperature, and available space.
[0024] Aluminum diethylphosphonate (AlPi) is a representative product of organophosphorus flame retardants. It has a high phosphorus content and good thermal stability. The phosphorus-containing free radicals generated during thermal decomposition can capture H· and OH· free radicals in the combustion chain reaction in the gas phase. Melamine polyphosphate (MPP) is a phosphorus-nitrogen intumescent flame retardant that forms a dense, expanded char layer in the condensed phase upon heating, isolating heat from oxygen. Magnesium hydroxide (MH) decomposes upon heating, absorbing heat and releasing water vapor, which dilutes combustible gases. The phosphorus-nitrogen-magnesium ternary compound can produce a synergistic flame retardant effect between the gas phase and the condensed phase. Silane coupling agents (such as γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane, the latter also known as γ-(2,3-epoxypropoxy)propyltrimethoxysilane, which are different names for the same compound) contain both hydrolyzable alkoxy groups and organic functional groups. The silanol groups produced by hydrolysis can condense with the hydroxyl groups on the surface of inorganic fillers, and the organic functional groups interact with the resin matrix, thereby improving the dispersibility and interfacial compatibility of inorganic flame retardants in the polymer matrix. This is the principle of surface modification. 2-Methylimidazolium zinc salt (a ZIF-8 type metal-organic framework compound) oxidizes zinc ions at high temperatures to form zinc oxide, creating a physical barrier. The imidazole skeleton decomposes to release non-flammable gases and catalyzes char formation in the condensed phase. Silane coupling agents and 2-methylimidazolium zinc salt can synergistically modify aluminum diethylphosphinate within a specific ratio range, constructing an organic-inorganic composite coating layer on the filler surface.
[0025] It should be noted that the following quantities are by weight. There are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: T2 copper busbar: thickness 1.2 mm, width 20 mm; saturated polyester resin: SK Chemicals ES-330, number average molecular weight 33000 g / mol, glass transition temperature 16℃; bisphenol A epoxy resin: E-51 type, epoxy equivalent 185-210 g / eq; bisphenol F epoxy resin: YDF-170, epoxy equivalent 160-180 g / eq; alicyclic epoxy resin: CELLOXIDE 2021P, epoxy equivalent 125-135 g / eq; the remaining raw materials are commercially available analytical grade or industrial grade reagents.
[0026] The preparation method of modified aluminum diethylphosphinate involved in Examples 1 to 3 and Comparative Examples 3 to 5 of this invention is as follows:
[0027] Take 100 parts of aluminum diethylphosphonate, 3 parts of γ-aminopropyltriethoxysilane and 1.5 parts of 2-methylimidazolium zinc salt, add them to 104.5 parts of deionized water, heat to 80℃, stir and react for 12 h, wash with ethanol, and dry under vacuum at 80℃ for 12 h to obtain modified aluminum diethylphosphonate.
[0028] Example 1: A method for fabricating a CCS busbar for an energy storage battery module, comprising the following steps:
[0029] S1: Take 75 parts of saturated polyester resin, 15 parts of bisphenol A type epoxy resin, 4 parts of blocked isocyanate, 9 parts of butanone and 9 parts of ethyl acetate, stir at 1000 rpm for 2 hours at 30℃ until completely dissolved, add 20 parts of modified aluminum diethylphosphinate, 15 parts of melamine polyphosphate, 7.5 parts of magnesium hydroxide and 2 parts of polymerized carbodiimide in sequence, and continue stirring for 1.5 hours until uniformly dispersed to obtain the adhesive coating liquid;
[0030] S2: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0031] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 150℃ and 2.0MPa for 120s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0032] Example 2: A method for preparing a CCS busbar for an energy storage battery module, comprising the following steps:
[0033] S1: Take 65 parts of saturated polyester resin, 20 parts of bisphenol F epoxy resin, 5 parts of blocked isocyanate, 10 parts of toluene and 10 parts of ethyl acetate, stir at 1000 rpm for 2 hours at 30°C until completely dissolved, then add 15 parts of modified aluminum diethylphosphinate, 20 parts of melamine polyphosphate, 10 parts of magnesium hydroxide and 2.5 parts of monocarbodiimide in sequence, and continue stirring for 1.5 hours until uniformly dispersed to obtain the adhesive coating solution;
[0034] S2: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0035] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 155℃ and 2.5MPa for 100s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0036] Example 3: A method for preparing a CCS busbar for an energy storage battery module, comprising the following steps:
[0037] S1: Take 80 parts of saturated polyester resin, 12 parts of alicyclic epoxy resin, 3 parts of blocked isocyanate, 7.5 parts of butanone and 7.5 parts of xylene, stir at 1000 rpm for 2 hours at 30°C until completely dissolved, then add 20 parts of modified aluminum diethylphosphinate, 8 parts of melamine polyphosphate, 4 parts of magnesium hydroxide and 1.5 parts of polymerized carbodiimide, and continue stirring for 1.5 hours until uniformly dispersed to obtain the adhesive coating liquid;
[0038] S2: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0039] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 145℃ and 1.8MPa for 150s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0040] Comparative Example 1: Aluminum diethylphosphonate modified only by a silane coupling agent was used, and the rest was the same as in Example 1. The specific steps are as follows:
[0041] S1: Take 100 parts of aluminum diethylphosphonate and 3 parts of γ-aminopropyltriethoxysilane, add them to 103 parts of deionized water, heat to 80℃, stir and react for 12h, wash with ethanol, and dry under vacuum at 80℃ for 12h to obtain modified aluminum diethylphosphonate.
[0042] S2: Take 75 parts of saturated polyester resin, 15 parts of bisphenol A type epoxy resin, 4 parts of blocked isocyanate, 9 parts of butanone and 9 parts of ethyl acetate, stir at 1000 rpm for 2 hours at 30℃ until completely dissolved, add 20 parts of silane coupling agent modified aluminum diethylphosphinate, 15 parts of melamine polyphosphate, 7.5 parts of magnesium hydroxide and 2 parts of polymerized carbodiimide, and continue stirring for 1.5 hours until uniformly dispersed to obtain the adhesive coating liquid;
[0043] S3: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0044] S4: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 150℃ and 2.0MPa for 120s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0045] Comparative Example 2: Unmodified aluminum diethylphosphonate (commercially available product, without any surface modification treatment) was used, and the rest was the same as in Example 1. The specific steps are as follows:
[0046] S1: Take 75 parts of saturated polyester resin, 15 parts of bisphenol A type epoxy resin, 4 parts of blocked isocyanate, 9 parts of butanone and 9 parts of ethyl acetate, stir at 1000 rpm for 2 hours at 30℃ until completely dissolved, then add 20 parts of aluminum diethylphosphinate, 15 parts of melamine polyphosphate, 7.5 parts of magnesium hydroxide and 2 parts of polymerized carbodiimide in sequence, and continue stirring for 1.5 hours until uniformly dispersed to obtain the adhesive coating liquid;
[0047] S2: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0048] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 150℃ and 2.0MPa for 120s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0049] Comparative Example 3: Aluminum diethylphosphonate: melamine polyphosphate: magnesium hydroxide = 6:3:1, the rest is the same as in Example 1, and the specific operation is as follows:
[0050] S1: Take 75 parts of saturated polyester resin, 15 parts of bisphenol A type epoxy resin, 4 parts of blocked isocyanate, 9 parts of butanone and 9 parts of ethyl acetate, stir at 1000 rpm for 2 hours at 30℃ until completely dissolved, add 24 parts of modified aluminum diethylphosphinate, 12 parts of melamine polyphosphate, 4 parts of magnesium hydroxide and 2 parts of polymerized carbodiimide in sequence, and continue stirring for 1.5 hours until uniformly dispersed to obtain the adhesive coating liquid;
[0051] S2: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0052] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 150℃ and 2.0MPa for 120s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0053] Comparative Example 4: No epoxy-modified resin, otherwise the same as in Example 1, the specific steps are as follows:
[0054] S1: Take 90 parts of saturated polyester resin, 4 parts of blocked isocyanate, 9 parts of butanone and 9 parts of ethyl acetate, stir at 1000 rpm for 2 hours at 30℃ until completely dissolved, add 20 parts of modified aluminum diethylphosphinate, 15 parts of melamine polyphosphate, 7.5 parts of magnesium hydroxide and 2 parts of polymerized carbodiimide in sequence, and continue stirring for 1.5 hours until evenly dispersed to obtain the adhesive coating liquid;
[0055] S2: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0056] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 150℃ and 2.0MPa for 120s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0057] Comparative Example 5: No anti-hydrolysis agent was added; all other steps were the same as in Example 1. The specific steps are as follows:
[0058] S1: Take 77 parts of saturated polyester resin, 15 parts of bisphenol A epoxy resin, 4 parts of blocked isocyanate, 9 parts of butanone and 9 parts of ethyl acetate, stir at 1000 rpm for 2 hours at 30°C until completely dissolved, add 20 parts of modified aluminum diethylphosphinate, 15 parts of melamine polyphosphate and 7.5 parts of magnesium hydroxide in sequence, and continue stirring for 1.5 hours until evenly dispersed to obtain the adhesive coating liquid;
[0059] S2: Using a doctor blade coating method, the adhesive coating liquid is coated on both sides of a biaxially oriented polyethylene terephthalate (PET) film with a surface tension of 44 mN / m and a thickness of 100 μm that has undergone corona treatment. Then, it is placed in an oven at 70℃, 90℃, and 110℃ for 2 min each to obtain a hot melt adhesive layer. A PET release film is then covered on the surface of the hot melt adhesive layer. The film is then wound up and slit to obtain a hot-pressed insulating film.
[0060] S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, T2 copper busbar, FPC signal acquisition layer, and hot-pressed insulating film in sequence on the positioning fixture. Send it into the hot press and hold it under pressure at 150℃ and 2.0MPa for 120s. Cool it to 55℃ and discharge it. Use laser lap welding to weld the sampling nickel sheet of the flexible printed circuit board signal acquisition layer to the copper busbar to obtain the CCS busbar.
[0061] Performance Testing: The CCS busbars obtained in the examples and comparative examples were tested according to GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test". The Limiting Oxygen Index (LOI) is a well-known indicator characterizing the flame retardant performance of materials. An LOI ≥ 27% is generally considered to indicate self-extinguishing properties, and an LOI > 35% is considered a high flame retardant level. Peel strength retention is a well-known indicator for evaluating the resistance of adhesive components to humid heat aging. It is generally considered that a peel strength retention ≥ 80% after 1000 hours of aging at 85℃ / 85%RH (double 85%) meets the reliability requirements of energy storage battery modules under long-term high humidity and high temperature conditions. (Referring to GB / T...) 2790-1995, "Test Method for 180° Peel Strength of Adhesives, Flexible Materials vs. Rigid Materials," describes a method for testing the peel strength of hot-pressed CCS busbars against tin-plated copper busbars. The hot-pressed CCS busbars are cut into 25mm wide samples. A 180° peel method is used at a peel speed of 50mm / min to test the peel force. Five samples are tested in each group, and the average value is taken as the adhesive strength. The samples are then aged in an 85℃, 85%RH constant temperature and humidity chamber for 1000 hours. The peel force is then tested again using the same method. The peel force retention rate (%) is calculated as: peel force after aging / initial peel force × 100%. The results are shown in Table 1 below.
[0062] Table 1
[0063]
[0064] Conclusion: As shown in the table above, the CCS busbar for energy storage battery modules and its preparation method of the present invention have the following significant innovations and beneficial effects:
[0065] As can be seen from Examples 1-3 and Comparative Examples 1-3, in Comparative Example 1, when aluminum diethylphosphonate was modified only by a silane coupling agent and not by 2-methylimidazolium zinc salt, the limiting oxygen index was 29.9% and the bonding strength was 1.52 N / mm; in Comparative Example 2, when aluminum diethylphosphonate was not modified, the limiting oxygen index was 28.2% and the bonding strength was only 1.40 N / mm; in Comparative Example 3, when the ratio of aluminum diethylphosphonate: melamine polyphosphate: magnesium hydroxide was 6:3:1, which deviated from the ratio range of (3-5):(2-4):(1-2) of the present invention, the limiting oxygen index was only 26.4% and the bonding strength was only 1.38 N / mm. The limiting oxygen index of Examples 1-3 is greater than 35%, and the bonding strength is greater than or equal to 1.82 N / mm, indicating that the present invention uses silane coupling agent and 2-methylimidazolium zinc salt to synergistically modify aluminum diethylphosphonate, which significantly improves the flame retardancy and bonding strength of CCS busbar.
[0066] As can be seen from Examples 1-3 and Comparative Examples 4-5, the peel strength retention rate in Comparative Example 4 without the addition of epoxy modified resin was only 54.8%, and the peel strength retention rate in Comparative Example 5 without the addition of anti-hydrolysis agent was also only 56.3%. However, the peel strength retention rate of the CCS busbars prepared in Examples 1-3 was greater than or equal to 86.6%. This indicates that the polyester-epoxy crosslinking network formed by the epoxy modified resin and the carbodiimide anti-hydrolysis agent worked together to delay the hydrolytic degradation process of the polyester and ensure the stability of the bonding strength of the CCS busbars under long-term high temperature and high humidity conditions.
[0067] In summary, this invention employs silane coupling agent and 2-methylimidazolium zinc salt to synergistically modify aluminum diethylphosphinate, strictly controls the ratio of aluminum diethylphosphinate, melamine polyphosphate, and magnesium hydroxide, and combines the combined effects of epoxy modified resin and carbodiimide anti-hydrolysis agent to improve the flame retardancy and bonding strength of CCS busbars, ensuring the stability of bonding strength of CCS busbars under long-term high temperature and high humidity environments.
[0068] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A CCS busbar for an energy storage battery module, characterized in that: The CCS busbar, from bottom to top, consists of a hot-pressed insulating film, a copper busbar, a signal acquisition layer, and another hot-pressed insulating film. The hot-pressed insulating film comprises a polyethylene terephthalate (PET) base film and a hot-melt adhesive layer. The hot-melt adhesive layer comprises the following components, by weight: 60-85 parts polyester resin, 10-25 parts epoxy modified resin, 30-60 parts flame-retardant filler, 1-3 parts anti-hydrolysis agent, 2-6 parts curing agent, and 10-25 parts solvent. The flame-retardant filler is composed of modified diethyl terephthalate. The modified aluminum diethylphosphonate is composed of aluminum phosphonate, melamine polyphosphate and magnesium hydroxide, and the mass ratio of the modified aluminum diethylphosphonate, melamine polyphosphate and magnesium hydroxide is (3~5):(2~4):(1~2); the modified aluminum diethylphosphonate is obtained by modifying aluminum diethylphosphonate with silane coupling agent and 2-methylimidazolium zinc salt, and the mass ratio of the modified aluminum diethylphosphonate, silane coupling agent and 2-methylimidazolium zinc salt is 100:(1~5):(0.5~3).
2. The CCS busbar for an energy storage battery module according to claim 1, characterized in that: The preparation method of the modified aluminum diethylphosphonate is as follows: (1) 100 parts of aluminum diethylphosphonate are added to 100-110 parts of deionized water and stirred to disperse; (2) 1-5 parts of silane coupling agent are added and stirred at 300-500 r / min for 20-40 min, and the temperature is raised to 60-70℃ and stirred for 1-2 h; (3) 0.5-3 parts of 2-methylimidazolium zinc salt are added, the temperature is raised to 70-80℃ and stirred for 2-12 h, filtered, washed with ethanol, and vacuum dried at 70-80℃ to obtain modified aluminum diethylphosphonate.
3. A CCS busbar for an energy storage battery module according to claim 2, characterized in that: The silane coupling agent is any one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.
4. A CCS busbar for an energy storage battery module according to claim 1, characterized in that: The polyester resin is a saturated polyester resin; the epoxy modified resin is any one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and alicyclic epoxy resin.
5. A CCS busbar for an energy storage battery module according to claim 1, characterized in that: The anti-hydrolysis agent is any one or more of polymeric carbodiimide and monocarbodiimide; the curing agent is a blocked isocyanate.
6. A method for preparing a CCS busbar for an energy storage battery module, characterized in that: The method for preparing the CCS busbar for an energy storage battery module according to any one of claims 1 to 5 includes the following steps: S1: Take polyester resin, epoxy modified resin, blocked isocyanate, and solvent, stir to dissolve, add flame retardant filler and anti-hydrolysis agent, stir evenly to obtain adhesive coating liquid. S2: Apply the adhesive coating liquid to one or both sides of the polyethylene terephthalate-based film, dry it to obtain a hot melt adhesive layer, cover the surface of the hot melt adhesive layer with a release film, and roll it up and cut it to obtain a hot-pressed insulating film. S3: Take the hot-pressed insulating film, peel off the release film, and stack the hot-pressed insulating film, copper busbar, signal acquisition layer, and hot-pressed insulating film in sequence. Hot-press, cool, discharge, and weld to obtain the CCS busbar.
7. The method for preparing a CCS busbar for an energy storage battery module according to claim 6, characterized in that: In S2, the drying temperature is 60~120℃, and the total drying time is 2~10min.
8. The method for preparing a CCS busbar for an energy storage battery module according to claim 6, characterized in that: In S3, the hot pressing temperature is 130~170℃, the hot pressing pressure is 1.0~3.0MPa, and the holding time is 60~180s.